2018
DOI: 10.1177/1474515118812252
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient–provider decision-making for use of anticoagulation for stroke prevention in atrial fibrillation: Results of the INFORM-AF study

Abstract: Background: Atrial fibrillation is associated with stroke, yet approximately 50% of patients are not treated with guideline-directed oral anticoagulants (OACs). Aims: Given that the etiology of this gap in care is not well understood, we explored decision-making by patients and physicians regarding OAC use for stroke prevention in atrial fibrillation. Methods and results: We conducted a descriptive qualitative study among providers (N=28) and their patients with atrial fibrillation for whom OACs were indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…None of the participants were involved in the decision-making process regarding OAC use. (34) In contrast to the results of these studies, the majority (61%) of participants in our study reported that they had engaged in the decision regarding OAC therapy initiation. Differences between these studies and ours could be explained by differences in sample size, sociodemographic and clinical characteristics of the respective study populations, and the approach used to assess patient engagement regarding OAC therapy.…”
Section: Discussioncontrasting
confidence: 94%
“…None of the participants were involved in the decision-making process regarding OAC use. (34) In contrast to the results of these studies, the majority (61%) of participants in our study reported that they had engaged in the decision regarding OAC therapy initiation. Differences between these studies and ours could be explained by differences in sample size, sociodemographic and clinical characteristics of the respective study populations, and the approach used to assess patient engagement regarding OAC therapy.…”
Section: Discussioncontrasting
confidence: 94%
“…[20,35,54,58,70,76,80,85] Reports from qualitative studies indicate that prescribers use formal stroke risk assessment tools but few use formal bleeding assessment tools. [79,86] Instead, prescribers rely on informal and subjective bleeding risk assessments.…”
Section: Physician-related Factorsmentioning
confidence: 99%
“…These include comorbidities, history of falls and bleeding, and age. [79,86,87] However, formal bleeding assessment tools such as HAS-BLED already consider comorbidities, prior history of bleeding, and age. [88] There may be a need to reassure physicians using findings such as that from a European registry-based study that indicated that the risk of stroke increases more than the risk of bleeding with advancing age, [89] and the fact that the risk of falls should not be the sole reason for withholding OACs.…”
Section: Physician-related Factorsmentioning
confidence: 99%
“…It gives insights in why particular phenomena occur or what underlying mechanisms are 1 . Over the past two years, the European Journal of Cardiovascular Nursing published 20 qualitative studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . These studies used methods such as content analysis, ethnography, or phenomenology.…”
Section: Introductionmentioning
confidence: 99%